Telecare call centre work and ageing in place - Procter, R; Wherton, J; Greenhalgh, P; Sugarhood, P; Rouncefield, M; Hinder, S (Springer, 2016)
We report findings from a study of call centre staff working to deliver a telecare service designed to enable older people to ‘age in place’. We show the steps they routinely take to produce a care system on behalf of their clients and their families that is both workable within the constraints of available resources and fit-for-purpose. In doing so, we have seen how call centre staff share with one another their experiences and solutions to problems, carry out liaison work with networks of lay carers, and generally act as the ‘glue’ providing the all-important link between otherwise fragmented services. We conclude with some thoughts on the significant technical and organizational challenges if the ‘ageing in place’ vision is to be realized in a practical, secure, dependable and cost-effective way.